PATHOGENESIS OF COLD ISCHEMIA IN CORONARY PATIENTS - A. P. Vasilyev; N. N. Streltsova; Y. N. Senatorov (Российский кардиологический журнал)
Biologically relevant structural changes in cell membranes (on an RBC model) at cold test, promoting its stabilization, has a pattern of pathology in coronary patients as taking place in membranes altered by atherogenesis. Profound changes in the lipid bilayer are followed by changes in intracardiac hemodynamics such as myocardial hyperfunction on one side and diastolic dysfunction with altered perfusion on the other side. These physiologically opposite tendencies may lie behind stress cold ischemia in coronary patients.